Enseignement de la littérature en République du Congo : quel sujet didactique forme-t-on à travers les prescriptions officielles ? - Samarange Romel Nzikou Mouelet; Ana Dias-Chiaruttini
Official prescriptions are a type of discourse with a constitutive value, meaning that it founds more than it is founded (Maingueneau, Cossutta, 1995). They are intended for an institutional audience (teachers, trainers, inspectors) and also for an audience outside the school institution, i.e. parents of pupils and anyone else wishing to know what should be taught in a school system. Researchers in the educational sciences, and in particular in didactics, analyse them as a discourse that enables us to understand implicit, ideological and political issues, issues that reveal how disciplines function. This article looks at prescriptive discourses in the Republic of Congo concerning the teaching of literature at secondary school level, in order to reconstruct the didactic subject who is formed, educated and institutionalised by these prescriptions. The aim is to understand what is taught under the term literature and the expected effects on 'the pupils'.